2007
DOI: 10.1068/p5262
|View full text |Cite
|
Sign up to set email alerts
|

Expertise in Pictorial Perception: Eye-Movement Patterns and Visual Memory in Artists and Laymen

Abstract: In two sessions with free scanning and memory instructions, eye-movement patterns from nine artists were compared with those of nine artistically untrained participants viewing 16 pictures representing a selection of categories from ordinary scenes to abstraction: 12 pictures were made to accommodate an object-oriented viewing mode (selection of recognisable objects), and a pictorial viewing mode (selection of more structural features), and 4 were abstract. The artistically untrained participants showed prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 17 publications
(24 reference statements)
7
143
1
6
Order By: Relevance
“…That is to say, they fixate mostly on recognizable objects, at the expense of background and framing elements and the relations among objects. Moreover, their liking is linked to the identity and meaning attached to those objects (e.g., Kapoula & Lestocart, 2006;Kapoula, Yang, Vernet, & Bucci, 2008;Nodine, Locher, & Krupinski, 1993;Vogt, 1999;Vogt & Magnussen, 2007;Zangemeister, Sherman, & Stark, 1995). While we cannot offer this as a conclusive explanation, the selective decrease in our art-naïve participants' liking for representational artworks following LO TMS might owe to TMS affecting processing of the individual objects depicted.…”
Section: Discussionmentioning
confidence: 58%
“…That is to say, they fixate mostly on recognizable objects, at the expense of background and framing elements and the relations among objects. Moreover, their liking is linked to the identity and meaning attached to those objects (e.g., Kapoula & Lestocart, 2006;Kapoula, Yang, Vernet, & Bucci, 2008;Nodine, Locher, & Krupinski, 1993;Vogt, 1999;Vogt & Magnussen, 2007;Zangemeister, Sherman, & Stark, 1995). While we cannot offer this as a conclusive explanation, the selective decrease in our art-naïve participants' liking for representational artworks following LO TMS might owe to TMS affecting processing of the individual objects depicted.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, expertise can affect various aspects of the ocular exploratory behaviour, such as the number, duration, and especially the spatial distribution of fixations. Such expertise-modulated gaze pattern differences have been observed between expert and novice observers when they look at pictures or art pieces (Zangemeister, Sherman, & Stark, 1995;Vogt & Magnussen, 2007;Humphrey & Underwood, 2009;Pihko et al, 2011), watch sports videos (Crespi, Robino, Silva, & de'Sperati, 2012), read music (Waters, Underwood, & Findlay, 1997), interpret medical images (Nodine, Kundel, Lauver, & Toto, 1996;Donovan & Manning, 2007;Kundel, Nodine, Krupinski, & Mello-Thomas, 2008;Matsumoto et al, 2011;Wood, Batt, Appelboam, Harris, & Wilson, 2014), drive (Underwood, 1998;Nabatilan, Aghazadeh, Nimbarte, Harvey, & Chowdhury, 2012), or play chess (Reingold, Charness, Pomplun, & Stampe, 2001). For instance, in comparison with laypersons, experienced radiologists tend to adopt a more global gaze strategy to 5 examine mammography images in detecting breast cancer (Kundel et al, 2008), arttrained viewers often scan a larger surface of representational paintings and give higher aesthetic rating when evaluating abstract paintings (Pihko et al, 2011), and the experienced drivers fixate more on the front and centre view, and make fewer driving errors when facing visual distraction (Nabatilan et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In particular, some authors reported that experts have more fixations of shorter duration than novices (Konstantopoulos 2009;Litchfield et al 2008). Others reported findings in the opposite direction (Bertrand and Thullier 2009;Vogt and Magnussen 2007). To account for effect size heterogeneity, the present study uses meta-analytic methods to cumulate individual research findings after controlling for sampling error; the goal was to evaluate three theories that account for expert superiority in visual domains.…”
mentioning
confidence: 95%
“…For example, expert radiologists are able to detect cancer in a mammogram in a split second (Kundel et al 2007), and to take a very different example, grandmasters locate the positions of checking pieces on the chessboard without moving the eye . Eye-tracking methodology has provided significant insight into some of the perceptual mechanisms underlying expert performance in a range of professional settings, including aviation (Schriver et al 2008), fish classification (Jarodzka et al 2010), car driving (Crundall et al 1999), arts (Vogt and Magnussen 2007), and sports (North et al 2009). In the present study, expert performance is understood as "consistently superior performance on a specified set of representative tasks for a domain" (Ericsson and Lehmann 1996, p. 277).…”
mentioning
confidence: 99%